KEPEMIMPINAN KETUA KELOMPOK TANI DALAM MENINGKATKAN DINAMIKA KELOMPOK DI KECAMATAN NATAR KABUPATEN LAMPUNG SELATAN - Fernaldi Shidi Hutomo; Irwan Effendi; Serly Silviyanti (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2018)
This study aimed to analyze the leadership level of the farmer group chairman, the dynamism level of the farmer group, the relation between farmer grup chairman’s leadership and group dynamics, in addition to the relation of group dynamics and rice productivity in Natar Sub-Distict of South Lampung Regency.  This study was conducted purposively in Natar Sub-District of South Lampung Regency by survey method, in which respondents consist of 69 farmer groups.  The data was collected in September - December 2016.    The data was analyzed descriptively and statistically, in which the relation between variables of this study were tested by Rank-Sperman Correlation Test.  The results showed that: the leadership level of the farmer group chairman in Natar Sub-District of South Lampung Regency was in good classification, the dynamics level of the group was in quite good classification.  The leadership of the farmer group’s chairman in Natar Sub-District was significantly related to the group dynamics, whereas group dynamics was not correlated significantly to productivity of rice in Natar Sub-Distric of South Lampung Regency.Key words : group dynamics, leadership, productivity of  rice